STUDI PENINGKATAN KARAKTERISTIK TANAH LEMPUNG DENGAN SERAT TANDAN KOSONG KELAPA SAWIT - Misnawati Misnawati (Lambung Mangkurat University Press, 2018)
Soil stabilization is intended to improve the properties of original soil by adding, among other things, a material that causes changes in the properties. In this study, it will use the empty fruit bunches fiber produced by the palm oil plantation industry. Fiber is the third largest amount after CPO and palm oil empty fruit bunches and fresh fruit bunches are estimated to contain 14-15%. This research was conducted to investigate the optimum percentage of fiber to get maximum density, to analyze the increase in soil CBR value after fiber addition, to analyze the increase in qu value in the soil UCT test after fiber addition, and to analyze the increase in su values ​​in the soil vane shear test after fiber addition. The study was conducted by mixing the fiber of palm oil's empty fruit bunches with soft clay soil with fiber content of 5%, 6%, 7%, and 8%, respectively. Based on the results of the analysis of this study, that the addition of palm oil's empty fruit bunches fibers in clay soil can improve the strength of the soil and the results of this study can be used as a reference for clay soil stabilization.